2016
DOI: 10.1186/s40064-016-3599-x
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of split-thickness skin graft using fast-clotting fibrin glue containing undiluted high-concentration thrombin or sutures: a comparison study

Abstract: ObjectiveFor skin defects caused by full-thickness burns, trauma, or tumor tissue excision, skin grafting is one of the most convenient and useful treatment methods. In this situation, graft fixation is important in skin grafting. This study was performed to compare the effectiveness of skin graft fixation between high-concentration fibrin sealant and sutures. There have been numerous studies using fibrin sealant for graft fixation, but they utilized slow-clotting fibrin sealant containing less than 10 IU/mL t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Despite the small cohort, lack of matched study participants, and short-term follow-up, the group anecdotally noted reduction in operating room duration, better hemostasis, and better graft fixation in the FG group. Han et al 31 developed a similar prospective study with 30-day follow-up, which found statistically significant reductions in collection formation and graft necrosis and increased graft take, with FG fixation methods. The group concluded that FG’s utility in STSG fixation was superior to suture- or staple-only fixation, despite the short-term follow-up analyses and lack of cost data.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small cohort, lack of matched study participants, and short-term follow-up, the group anecdotally noted reduction in operating room duration, better hemostasis, and better graft fixation in the FG group. Han et al 31 developed a similar prospective study with 30-day follow-up, which found statistically significant reductions in collection formation and graft necrosis and increased graft take, with FG fixation methods. The group concluded that FG’s utility in STSG fixation was superior to suture- or staple-only fixation, despite the short-term follow-up analyses and lack of cost data.…”
Section: Discussionmentioning
confidence: 99%
“…In the plastic surgery literature, fibrin glue has been used for haemostasis at skin grafting donor sites in two RCTs, one of which reported a small beneficial effect and the other no effect. In the burns literature, several groups have reported improved wound healing, graft adherence, reduced blood loss and improved haemostasis with fibrin glue. Additional advantages may include the use of fibrin glue for skin graft attachment in areas that are hard to graft such as the face, eyelids and ears, and areas of high mobility, use in diabetics and smokers, and improved functional outcomes with fibrin glue use.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin glue has been described widely for skin grafting, most extensively for SSG attachment following burn surgery. Studies suggest a number of benefits, including improved graft take, reduced haematoma formation, improved donor‐site haemostasis and improved functional outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Fibrin is often applied in regenerative medicine to support wound healing. To accelerate wound healing, fibrin is mostly used in the form of a sealant, 4,5 a gel, [6][7][8] a glue, 9,10 or microbeads. 11 It is directly applied into the wound and is seeded with skin cells.…”
Section: Introductionmentioning
confidence: 99%